Human Neutrophil'S Chemotaxis and Intracellular Killing in Response to Type 1 Piliated Uropathogenic Escherichia Coli - N Nooritalab; SH Najar Peerayeh (Tehran University of Medical Sciences, 2007)
Introduction: Uropathogenic Escherichia coli (UPEC), the commonest cause of urinary tract infections, bind to target cells and phagocytes via several distinct pairs of adhesins and receptors. In some cases bacterial binding to phagocytes ends to bacterial elimination. The survival and spread of bacteria in infected tissues are determined by the resistance of bacteria to elimination by phagocytic cells like neutrophils. The aim of this study was to determine the role of type 1 pili in interaction of UPEC with human neutrophils and its effect on bacterial killing. Methods: We used 3 clinical and 1 standard strains of type 1 piliated and 1 unpiliated standard strain of UPEC. Type 1 piliated and unpiliated strains (obtained by growth at a pilus-restrictive temperature) of UPEC were used for determining the effect of this pili on migration of neutrophils towards bacteria in Boyden chamber. Also intracellular killing of bacteria by human neutrophils was estimated by counting of the number of viable bacteria in 45 minutes after incubation of piliated and unpiliated strains with purified neutrophils.The results were analyzed with t-test. Results: In chemotaxis assay, PMN migration towards piliated strains was 46-73% of that observed with FMLP, but it was 34-41% in unpiliated strains.The results obtained showed that type 1 piliated UPEC stimulated significantly greater chemotaxis than did unpiliated ones(P